STUDI TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS STRATEGI BERSAING UNTUK MENINGKATKAN KINERJA PERUSAHAAN PADA KUKM PENGRAJIN KULIT DI MANDING - BANJUL - Barokah, Siti Nur (JURNAL BISNIS STRATEGI, 2009)
In a context of enhancing the competitive advantage, acquiring knowledge is an important factor This point is the weakest of the KUKM powerlessness. The problem that Group of Small Business and Entrepreneurs often face basically is on the decision making onCompetitive Strategy in order to enhance the firms' performance. Therefore, it is necessary to examine "How to enhance the Group of Small Business and Entrepreneurâ€™s performance, by focusing on Competitive Strategy and the affecting factors." Hence, a model that consists of five variables is developed. Those five variables are strategic assets, environment adaptability, entrepreneurship orientation, competitive strategy and firms' performance.Data of observed variables is collected through questionnaire. The questionnaire is specially developed to have structured questions about the variables. 100 respondents of owners or people who run leather crafts in Yogyakarta were asked to answer the questionnaires. Then, data collection is analyzed with Structural Equation Modeling (SEM) method.The test result of the model shows that the model developed in this researched is proven to be fit. While the hypothesis test shows that the quality at strategic asset; environmental adaptability, and the quality of competitive strategy has a positive and significant effect on firms' performance.Based on the hypothesis result, enhancing Group of Small Business and Entrepreneurs performance can be achieved by making better the competitive strategy through entrepreneurship orientation.Â